Systematic significance of cypselae in the Calea teucriifolia complex - Marques, Danilo; Resende Bueno, Vinícius; Magalhães Teles, Aristônio; Marzinek, Juliana (Phytotaxa, 2022)
The Calea teucriifolia group is composed by four species of the tribe Neurolaeneae (Asteraceae). Despite numerous attempts to taxonomically understand this group of species through macromorphological characters, no progress has been made due to the overlapping of these characters. Therefore, we propose to evaluate the taxonomic values of cypselae morphology and anatomy for this group. Studies focused on cypsela have represented an advance, since patterns of phytomelanin deposition, pericarp and pappus morphology have allowed classifications within Asteraceae. Our results demonstrate that the cypselae of the analyzed group have a high morphological uniformity. Hence, cypsela morphology does not have characters that support separation of the species. However, the patterns of phytomelanin deposition in this group represent an anatomical novelty in Calea, and perhaps, in Neurolaeneae. The Calea teucriifolia group has the same deposition pattern observed in the tribe Eupatorieae. New systematic approaches are needed to solve taxonomic questions in the Calea teucriifolia group, and an expansion of the cypsela anatomical studies of the Neurolaeneae genera could demonstrate whether the Eupatorieae phytomelanin pattern of deposition could correspond to an apomorphy for the tribe.